(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Geosynthetics have been successfully used for decades in the construction of roads. They fulfil almost all classical function like separation, protection, filtration. Drainage, sealing, and reinforcement. In recent time the scope of application has been extended significantly by the construction of road pavement. Field evidences indicate that geosynthetic reinforcements can improve pavement performance by avoiding cracking, rutting, patholes by reducing deflection of road surface.